E-Learning Berbasis Moodle Sebagai Media Informasi, Teknologi Dan Komunikasi Guna Mencegah Penyebaran COVID-19 - Agus Zainudin (JIEES : Journal of Islamic Education at Elementary School, 2020)
Since the effort to prevent Corona Virus Disease 2019 (COVID-19) in the form of social and physical distance control in various lines of life. The policy is based on the number of victims which continues to grow and its distribution increasingly difficult to control in Indonesia. Especially after the government has reacted successively with various actions such as establishing alert status, disaster emergencies, non-natural disasters, extension of disaster emergency status to large-scale social restrictions (PSBB). The policy, the Minister of Education and Culture of the Republic of Indonesia immediately made a derivative policy in the field of education through the Circular of the Minister of Education and Culture No. 3 of 2020 concerning Prevention of COVID-19 in the Education unit, all education from elementary school to tertiary level in Indonesia to take decisive steps on the appeal of the government to carry out learning activities based on E-Learning. For the sake of implementing E-Learning, efforts such as application-based learning began to be applied. In the midst of this pandemic COVID-19 is ready or not, has opened the public's eye to creative and adaptive thinking by changing the model of teaching and learning activities that were initially based on conventional learning into learning based on e-learning and making new breakthroughs, from the normative paradigm of the real world to the virtual world with utilizing technology in every teaching and learning process.